Gastropods associated with Fossil Traces from Yacoraite Formation(Maastrichtian-Danian), and its Paleoenvironmental Significance, Jujuy, Northwestern Argentina - Cónsole Gonella, Carlos Alfredo (2009)
We present results tending to characterize the new records of invertebrates from the Yacoraite Formation (Maastrichtian-Danian). The fossils reported come from two stratigraphic sections exposed in the surroundings of Maimará and Jueya, province of Jujuy, northwestern Argentina. The selection was based on geological and paleontological evidence. The recovered fossils include gastropods and invertebrate fossil traces, including Planolithes, Skolithos, and Gastrochaenolithes ichnogenus. As a result of our review, we discussed the possibility of assigning the described gastropods to the family Zygopleuridae (gen. et sp. indet.) as an approximation to the taxonomic resolution of this fossil fauna. The trace fossils were assigned to the archetypical Glossifungites ichnofacies. The study of the fossil assemblage allowed us to define a shallow depositional environment, characteristic of a marine environment with high-energy conditions.